Oceanographic and behavioural processes affecting invertebrate larval dispersal and supply in the western Iberia upwelling ecosystem - Queiroga, Henrique
The present review addresses recent findings made in the western Iberia ecosystem on the behavioural and physical interactions that regulate dispersal, supply to coastal habitats and settlement of invertebrate larvae. These studies used the barnacle Chthamalus spp. and the crab Carcinus maenas as model organisms. The observations made on the Iberian shelf showed extensive diel vertical migrations along the water column by representatives of both groups that have never been reported before. The interaction of the diel vertical migration with the two-layer flow structure of upwelling/downwelling circulation suggests a mechanism that may help to retain larvae in shelf waters during upwelling conditions. Measurements of daily supply of C. maenas megalopae to estuaries separated by 500 km disclosed a semilunar pattern, with highest supply around highest amplitude tides, indicating that supply of megalopae to estuaries is accomplished by selective tidal stream transport. Relaxation of equatorward winds also played a role in supply, by enhancing translocation of megalopae to the nearshore. Concerning Chthamalus larvae, the observations on daily settlement made at rocky shores also separated by 500 km showed unclear patterns between locations and years. The relationship of settlement with water temperature, tidal range and upwelling indices indicated that supply of barnacle cyprids may be controlled by multiple mechanisms, viz. upwelling/downwelling circulation, internal tidal bores and sea breezes.